2013
DOI: 10.1177/0885328213481637
|View full text |Cite
|
Sign up to set email alerts
|

Differential stimulation of neurotrophin release by the biocompatible nano-material (carbon nanotube) in primary cultured neurons

Abstract: In order to develop novel, effective therapies for central nervous system regeneration, it is essential to better understand the role of neurotrophic factors and to design, accordingly, better artificial scaffolds to support both neurite outgrowth and synapse formation. Both nerve growth factor and brain-derived neurotrophic factor are major factors in neural survival, development, synaptogenesis, and synaptic connectivity of primary cultured neurons. As a prime candidate coating material for such neural cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Kim et al . reported in 2014 that neurons cultivated on CNT-coated surfaces initiate their neurite outgrowth one to two days later than on standard coatings [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kim et al . reported in 2014 that neurons cultivated on CNT-coated surfaces initiate their neurite outgrowth one to two days later than on standard coatings [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, CNTs have been shown in some studies to serve as an extracellular matrix for neurons and to direct neurite outgrowth, regulate neurite branching as well as to provide adhesion points for neurons [ 15 ]. This makes CNTs a promising matrix for primary neuronal cell cultures [ 16 ] as an alternative to other established matrices (e.g. matrigel, laminin or poly-D/L-ornithine).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…exposure to CNTs, specially MWNTs. An in vitro investigation showed that CNTs did not change BDNF expression levels in primary cultured neurons on CNTs-coated coverslips but stimulated BDNF release into the media (Kim et al, 2008). Nowadays, CNTs are used as artificial scaffolds to support neurite outgrowth and synapse formation, but exact mechanisms underlying interactions of CNTs and neurotrophic factors as therapeutics in disorders of central nervous system are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…CNT-layered substrates are biocompatible and efficient in inducing stem cells to differentiate specifically to neurons [17][18][19] , promoting neurite outgrowth 20 , and enhancing synaptogenesis [21][22][23] and consequential development of neuronal network 24,25 .…”
Section: Introductionmentioning
confidence: 99%